Exit vs. Voice - Eleonora Broccardo; Oliver D. Hart; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2021)
We study the relative effectiveness of exit (divestment and boycott) and voice (engagement) strategies in promoting socially desirable outcomes in companies that generate externalities. We show that if the majority of investors are socially responsible, voice achieves the socially desirable outcome, while exit does not. If the majority of investors are purely selfish, exit is a more effective strategy, but neither strategy generally achieves the first best. We also show that individual incentives to join an exit strategy are not aligned with social incentives, and hence exit can lead to a worse outcome than if all individuals are purely selfish.
Keywords: D02; D21; D23; D62; D64; H41; L21; 330; Exit; Voice; Social Responsibility; Divestment; Boycott; Engagement